WHATSAPP VOICE CHAT (WVC) AS AN EFL ONLINE LEARNING MEDIA AT ENGLISH CLUB OF SMPIT INSAN KAMIL SIDOARJO - Adia Budjana; Lina Aris Ficayuma (Journal of English Language Teaching and Islamic Integration, 2024)
The objective of this study was to figure out the steps of implementation one of the features of the Whatsapp Messenger application, namely Voice chat as an online learning media for students at English club of  SMPIT Insan Kamil Sidoarjo. The method used in this research is descriptive qualitative method. The population in this study were all English Club members of SMPIT Insan Kamil Sidoarjo. The sample of this research is a chairman and 20 members of the English Club, as well as eight  members to find out the student's response. In this study, there were three stages, the first was pre-activity. at this stage, the teacher provides material reinforcement during class learning. The second is the Whilst activity, at this stage the teacher gives instructions using Whatsapp text combined with Whatsapp voice notes. At this stage students also implement the instructions given by the teacher using Whatsapp voice notes. After that, students fill out the submission list sent by the teacher. The third stage is the closing activity, in this activity the teacher provides feedback in the form of evaluating and appreciating the results of student performance. In student responses, it was found that  six  out  of  eight  students  interviewed  stated  that  they  felt  happy  with  the  online  learning through Whatsapp voice chat. Suggestions for other researchers to investigate the effectiveness of using features such as video calling to improve students' English skills.